Peran Pempublikasian Serta Inovasi Produk Dan Jaringan Bisnis Pada Konveksi RKM Garmenindo - Resya Dwi Marselina; Rahman Sidik; Mahadi Maulana; Rasis Utomo; Ali Rohman; Alan Sutisna (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The aim of this research is to find out how the network is formed and managed, to find out what products are produced and what the marketing system is like at RKM GARMENINDO. The research method used is qualitative with a descriptive approach. Through this research method, researchers find knowledge about research at a certain time. The results obtained in this research are CV which is engaged in making high quality clothes for various clothing models including shirts, trousers and t-shirts with several other models. RKM GARMENINDO ensures that every product they make has guaranteed quality and creative models. The conclusion of this research is that suppliers for raw materials or basic materials, namely fabric, only take from 1 supplier who is trusted so that the quality and cleanliness of the material is maintained and the distribution of parties that collaborate with UMKM Rkm Garmenindo only shops around the Bandung area, and only 3 The places that are always distributed are the shops in the Alun-alun, Tegalega and Cijerah areas. From the production aspect, there are only 3 products that are most popular with customers, namely shirts, t-shirts and men’s shorts. Suggestions expand distribution from region to region in the city and utilize social media to open an online shop. Increase the number of products that are innovative and can keep up with today’s market and have the unique characteristics of each product produced by UMKM Rkm Garmenindo.